2009
DOI: 10.1590/s1516-89132009000400018
|View full text |Cite
|
Sign up to set email alerts
|

The influence of caffeine and thymol on the survival, growth and reproduction of Subulina octona (Brugüière, 1789) (Mollusca, Subulinidae)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 18 publications
1
6
0
2
Order By: Relevance
“…According to these authors, the hatches occur between the first and the 15 th day after the oviposition, with registered mean viability of the eggs (94.8%) for this snail. The average mean of hatching in groups exposed for 48 hours was similar to the means found by Ferreira et al (2009). Those authors tested the ovicidal activity of a caffeine solution at 5 g/L in S. octona and obtained an average hatching of 12.5%.…”
Section: Discussionsupporting
confidence: 80%
“…According to these authors, the hatches occur between the first and the 15 th day after the oviposition, with registered mean viability of the eggs (94.8%) for this snail. The average mean of hatching in groups exposed for 48 hours was similar to the means found by Ferreira et al (2009). Those authors tested the ovicidal activity of a caffeine solution at 5 g/L in S. octona and obtained an average hatching of 12.5%.…”
Section: Discussionsupporting
confidence: 80%
“…This monoterpene has already had its insecticide, bactericide, fungicide, and molluscicide potential evidenced by different authors (Imdorf et al 1995;Mansour et al 2000;Ferreira et al 2009), though its acaricide effect was only demonstrated recently for immature of R. (B).microplus (Novelino et al 2007a, b), Rhipicephalus sanguineus (Latrelle 1906) (Acari: Ixodidae) Monteiro et al 2009). Its repellent activity on tick larvae of the bovine was also demonstrated by Novelino et al (2007b).…”
Section: Introductionmentioning
confidence: 98%
“…Various articles have described this monoterpene's potential as a bactericide, fungicide, nematicide, molluscicide, insecticide and acaricide against different target species and with different formulations (Imdorf et al 1995;Mansour et al 2000;Tsao and Zhou 2000;Ferreira et al 2009;Pandey et al 2009;Baggio et al 2004).…”
Section: Introductionmentioning
confidence: 99%